PENGARUH ROTASI DAN MUTASI TERHADAP KINERJA KARYAWAN IAIN CURUP - Topan Alparedi (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research evaluates the impact of transfers and rotations on the performance of IAIN Curup employees regarding human resource management by offering alternatives to improve employee performance. The object of the research is the employees of IAIN Curup. Cluster Random Sampling was used to determine the research respondents because the research population comes from various units, with employees representing the units acting as samples. The total number of samples was 101. To test the influence of rotation and mutation on employee performance, this study uses quantitative analysis with several levels of statistical tests, and to determine how rotation and mutation affect the performance of IAIN Curup employees, multiple linear regression is used. The test results for the independent variable, the rotation variable (X1), obtained a Sig. value of 0.012 and the mutation variable a Sig. value of 0.000, while in the test using an alpha of 0.05, this means the decision is to reject Ho and accept Ha, which can be interpreted that rotation and mutation have a positive and significant effect on employee performance and both hypotheses are proven. Based on the research, several conclusions can be drawn from this study: (1) Rotation has a significant impact on the performance of IAIN Curup employees. This proves that for existing positions, providing skill development and clear career management will improve employee performance. (2) Mutation has a significant impact on the performance of IAIN Curup employees. This shows that with proper implementation of mutation, performance will improve.